PENGARUH BAURAN PEMASARAN DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK PAKAIAN DI BARATA KOTA BIMA - Erick Dala Oscar; Irma Mardian (JEBIM Prima, 2021)
This research is an associative research, namely research that aims to determine the influence of the marketing mix and service quality partially and simultaneously on purchasing decisions for clothing products. This research was conducted in Barata, Bima city. The research instrument used is a questionnaire containing a number of questions about the marketing mix, service quality and purchasing decisions for clothing products. The population used is all consumers who buy clothing products in Barata, Bima city, the population is unknown (population unknown). Therefore, to determine the number of samples using the unknown population formula in order to obtain 96 respondents. The sampling technique used is accidental sampling, namely Barata consumers who happen to meet with researchers can be used as samples tailored to the needs of researchers. Data collection techniques used in this study are: observation, heritage studies and documentation. The data analysis techniques used are validity, reliability, classical assumption test, multiple linear regression, multiple correlation coefficient, t test (partial) and simultaneous f test. The results of this study indicate that the marketing mix partially has no effect on purchasing decisions for clothing products in Barata, service quality partially affects purchasing decisions for clothing products in Barata, but the marketing mix and service quality simultaneously affect purchasing decisions for clothing products in Barata.